Reconciliation of matrimonial disputes: the constrains and proposed reform - Ali Mohamed, Ashgar Ali (2007)
In matrimonial disputes, pursuant to the Law Reform (Marriage and Divorce) Act 1976, s 55(1), the petitioner , before the presentation of a petition for dirvoce, shall have recourse to the assistance and advice of such persons or bodies as may be made available for the purpose of effecting reconciliation between parties to a marriage who have become estranged. Section 106 of the Act further provides that no person shall petition for divorce, except for dissolution by mutual consent (s. 52) and under s. 53,unless he or she has first referred the matrimonial difficulty to a conciliatory body known as a 'Reconciliation Tribunal'. In other words, reconciliation is a prerequisite for the filing of a divorce petition in court. The dispute would be referred to a conciliatary body and the members of this body consist of laymen who are usualy respectable members of the community. The body will iitiate attempts to resolve the matrimonial difficulty to the satisfaction of the parties. If the body is unable to effect reconciliation it shall issue a certificate to that effect and may append to the certificate such recommendations as it thinks fit in relation to maintenance of wife and children, custody of the children (if any), on division of property, and other matters related to the marriage. Section 106(5)(c) of the Act provides that no advocate or solicitor shall appear or act as such for any party in any proceeding beforea consiliatory body and no party shall be represented by any person, other than a member of his or her family, without the leave of the conciliatory body. Unfortunately, however, the success rate of amicable settlement of matrimonial disputes in the 'Reconciliation Tribunal' is way below the satisfactory level. One wonders whether that tribunal is set up with a view to help resolve disputes between conflicting couples or is it just a rubber stamp to be obtained as one of the processes to be overcome before the dissolution of the marriage can be obtained. In this paper, the writer will attempt to identify the reasons why the tribunal fails to achieve its objective and will propose viable suggestions to overcome it.